The power of in situ pulsed laser deposition synchrotron characterization for the detection of domain formation during growth of Ba0.5Sr0.5TiO3 on MgO. (24th January 2014) - Bauer, Sondes; Lazarev, Sergey; Molinari, Alan; Breitenstein, Andreas; Leufke, Philipp; Kruk, Robert; Hahn, Horst; Baumbach, Tilo
<x xml:space="preserve">Abstract</x> A highly sophisticated pulsed laser deposition (PLD) chamber has recently been installed at the NANO beamline at the synchrotron facility ANKA (Karlsruhe, Germany), which allows for comprehensive studies on the PLD growth process of dielectric, ferroelectric and ferromagnetic thin films in epitaxial oxide heterostructures or even multilayer systems by combining in situ reflective high‐energy diffraction with the in situ synchrotron high‐resolution X‐ray diffraction and surface diffraction methods. The modularity of the in situ PLD chamber offers the opportunity to explore the microstructure of the grown thin films as a function of the substrate temperature, gas pressure, laser fluence and target–substrate separation distance. Ba0.5Sr0.5TiO3 grown on MgO represents the first system that is grown in this in situ PLD chamber and studied by in situ X‐ray reflectivity, in situ two‐dimensional reciprocal space mapping of symmetric X‐ray diffraction and acquisition of time‐resolved diffraction profiles during the ablation process. In situ PLD synchrotron investigation has revealed the occurrence of structural distortion as well as domain formation and misfit dislocation which all depend strongly on the film thickness. The microstructure transformation has been accurately detected with a time resolution of 1 s. The acquisition of two‐dimensional reciprocal space maps during the PLD growth has the advantage of simultaneously monitoring the changes of the crystalline structure as well as the formation of defects. The stability of the morphology during the PLD growth is demonstrated to be remarkably affected by the film thickness. A critical thickness for the domain formation in Ba0.5Sr0.5TiO3 grown on MgO could be determined from the acquisition of time‐resolved diffraction profiles during the PLD growth. A splitting of the diffraction peak into two distinguishable peaks has revealed a morphology change due to modification of the internal strain during growth.